Pengelolaan Sumber Daya Insani yang Profesional Melalui Peningkatan Tauhid - Wardani, Ali; Zulhikam, Akhmad; Agustan, Agustan; Amir, Sudirman Andi; Sirajuddin, Sirajuddin (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2024)
Human resources are very important in sharia entrepreneurship. This section plays an important role as the executor of all business affairs. Therefore, professional human resources are really needed in sharia entrepreneurship. This short article will discuss the main basics in building professional human resources. Starting from the basic principles to the application or application in forming professional human resources will be discussed in a coherent manner so that it is easy to understand. The aim is to provide clear information to readers about professional human resources, their important role in business and how to obtain them.